Epidemiological profile of breast cancer in Brazil from 2010 to 2020 (Research, Society and Development, 2024)
In Brazil, cancer is the second leading cause of death, surpassed only by cardiovascular diseases. Breast cancer is the second most common neoplasm in Brazil, and the first cause of death from neoplasia in women and can affect both men and women when exposed to genetic and environmental factors. The present study aims to investigate the epidemiological profile of breast cancer deaths in Brazil in the period between 2010 and 2020. The study was carried out using a descriptive cross-sectional design, in which data was provided by the Information System on Mortality associated with death certificates (SIM-DO) provided by the SUS Information Technology Department (DATASUS). The data were analyzed using the R programming language and the RStudio program. There was a total of 163,579 deaths due to breast cancer between 2010 and 2020, 98.9% of which were in the female population, with a progressive increase in the interval, with an average of 15,739.91 deaths per year. It was found that the highest concentration of outcomes occurred in the Southeast (51.06%), in the population aged between 50 and 59 (20%), in white individuals (61.68%), married, and aged 8 to 11 years of study concerning educational level.